2012
DOI: 10.1038/nchembio.925
|View full text |Cite
|
Sign up to set email alerts
|

Reversible targeting of noncatalytic cysteines with chemically tuned electrophiles

Abstract: Targeting noncatalytic cysteine residues with irreversible acrylamide-based inhibitors is a powerful approach for enhancing pharmacological potency and selectivity. Nevertheless, concerns about off-target modification motivate the development of reversible cysteine-targeting strategies. Here we show that electron-deficient olefins, including acrylamides, can be tuned to react with cysteine thiols in a rapidly reversible manner. Installation of a nitrile group increased the olefins’ intrinsic reactivity, yet pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
505
0
16

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 454 publications
(543 citation statements)
references
References 28 publications
22
505
0
16
Order By: Relevance
“…Covalent targeting of cysteine residues within the ATP binding pocket is an effective way to obtain highly potent and selective kinase inhibitors with long target residence time (24,25). Ibrutinib, for instance, irreversibly binds cysteine 481 in BTK and cysteine 442 in ITK, leading to a blockade of signaling downstream of the B-cell receptor and TCR, respectively.…”
Section: Il-2-inducible T-cell Kinase (Itk)mentioning
confidence: 99%
“…Covalent targeting of cysteine residues within the ATP binding pocket is an effective way to obtain highly potent and selective kinase inhibitors with long target residence time (24,25). Ibrutinib, for instance, irreversibly binds cysteine 481 in BTK and cysteine 442 in ITK, leading to a blockade of signaling downstream of the B-cell receptor and TCR, respectively.…”
Section: Il-2-inducible T-cell Kinase (Itk)mentioning
confidence: 99%
“…[123] This suggested that the conjugate addition to such electrophiles was reversible, and this was conclusively demonstrated by Serafimova et al in 2012. [124] This reversibility was thought to arise from the increased acidity of the αC-H protons, and in accordance with this the Michael addition to acrylates, acrylonitriles and acrylamides was found to be irreversible, resulting in the generation of stable thioether bonds.…”
Section: Hplc Studies To Determine Reaction Irreversibilitymentioning
confidence: 66%
“…[123] This suggested that the conjugate addition to such electrophiles was reversible, and this was conclusively demonstrated by Serafimova et al in 2012. [124] This reversibility was thought to arise from the increased acidity of the αC-H protons, and in accordance with this the Michael addition to acrylates, acrylonitriles and acrylamides was found to be irreversible, resulting in the generation of stable thioether bonds. [124] Surprisingly, the reaction between enones and thiols was found to be freely reversible under physiological conditions and was used by Greaney et al to probe glutathione S-transferases using a dynamic combinatorial approach.…”
Section: Hplc Studies To Determine Reaction Irreversibilitymentioning
confidence: 66%
See 1 more Smart Citation
“…There are application reports exemplifying methyl 2-cyano-3-phenyl-2-propenoate, MCPP [1,2]. Thus, ring-unsubstituted MCPP was employed in studies of beta amino acid-modified and fluorescently labeled kisspeptin analogues with potent KISS1R activity [1] and in reversible targeting of noncatalytic cysteines with chemically tuned electrophiles [2]. Methoxy ring-substituted MCPP was used in photorefractive polymer composites [3] as well as in synthesis of new triazoles for potential antifungal agents applications [4].…”
Section: Introductionmentioning
confidence: 99%